Annotations in Scholarly Editions and Research Functions, Differentiation, Systematization - Nantke, Julia; Schlupkothen, Frederik (De Gruyter, 2020)
The notion of annotation is associated in the Humanities and Information Sciences with different concepts that vary in coverage, application and direction of impact, but have conceptual parallels as well. This publication reflects on different practices and associated concepts of annotation, puts them in relation to each other and attempts to systematize their commonalities and divergences in an interdisciplinary perspective.